Game Theory - Durlauf, Steven N. author. aut Link
XI, 379 p.
Keywords: Specially selected from The New Palgrave Dictionary of Economics 2nd edition, each article within this compendium covers the fundamental themes within the discipline and is written by a leading practitioner in the field. A handy reference tool.